2015
DOI: 10.1021/acs.jpcc.5b03292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Molecular Weight on Molecular Ordering and Proton Transport in Organized Sulfonated Polyimide Thin Films

Abstract: The effect of molecular ordering and ordered domain size on molecular weight dependent proton conductivity in well-organized sulfonated polyimide (SPI) thin films has been investigated using both low molecular weight (LM w , M w = 1.3 × 10 4 ) and high molecular weight samples (HM w , M w = 2.6 × 10 5 ). Analyses of the films by grazing incidence small-angle X-ray scattering (GISAXS) revealed that the HM w SPI film exhibits the higher degree of inherent liquid crystalline-like lamellar ordering, and that it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 38 publications
0
39
1
Order By: Relevance
“…In our previous study of the GI-SAXS measurements (Figure 4b), a self-assembled lamellar structure parallel to the substrate surface has been determined in the planar ASPI-2 thin film. 22,24 This lamellar distance expands linearly to the out-ofplane direction by water uptake. Furthermore, molecular ordering improves by water uptake based on the lyotropic LC property (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study of the GI-SAXS measurements (Figure 4b), a self-assembled lamellar structure parallel to the substrate surface has been determined in the planar ASPI-2 thin film. 22,24 This lamellar distance expands linearly to the out-ofplane direction by water uptake. Furthermore, molecular ordering improves by water uptake based on the lyotropic LC property (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier study demonstrated that the degree of molecular ordering strongly affects proton conductivity. 24 To reveal the origin for the high proton conductivity in both planar and bent ASPI thin films, POM, GISAXS, and pMAIR measurements were carried out.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular weight is another useful parameter to enhance ASPI thin film proton conductivity [100]. In general, the molecular weight of proton-conductive polymers contributes to mechanical strength, but it does not contribute to proton conductivity.…”
Section: Highly Proton-conductive Polymer Thinmentioning
confidence: 99%